Performance evaluation of nationalized barangay high schools in Region IX - Jawali, Hamsali S. 1947-
Muslim and Christian administrators, teachers, non-teaching personnel and members of school boards provided data which indicated that nationalized barangay high schools performed far from satisfactorily. Half of the schools do not meet the enrolment guideline of 300 students; physical plant, facilities and instructional materials are inadequately provided due to insufficient financial allocations; 3 out of 4 do not own the school sites; schools have adequate teaching and non-teaching personnel but no health personnel; the schools' participation and survival rates are low; dropout rate, graduation rate and NCEE performance show that the schools have a long way towards improving the quality of their educational products.